Regulation of Auxin signaling in plants during stress response; A molecular genetics study on Aux/IAA transcription repressor gene family - Dhanapala, M.P.C.S. (Faculty of Science, University of Colombo, 2018)
Plants cope with changing biotic and abiotic environment by acclimation of their growth and development to prevailing conditions. The developmental plasticity of the plants to cope with changing environmental conditions requires a diverse integration of growth performances with signal perception and transduction systems. The plant hormone auxin regulates virtually every aspect of plant growth and development in responses to environmental cues and pathogenic attacks. Plants interpret auxin signals through a short nuclear signaling pathway, in which auxin binding stabilizes the interaction between auxin receptors and a group of transcriptional repressors called Aux/IAAs. Among the four domains of Aux/IAAs, domain II is critical for the own degradation of protein, in response to auxin. Auxin is known to play a major role in stress tolerance mechanisms in plants along with Ca2+. Calcium signal is transduced in cells through a number of Ca2T sensing molecules including Calmodulin (CaM). CaM interacts with SAURs, which is an early auxin response gene. However, the lack of proper information on molecular biological mechanisms involved in auxin-dependent growth performance of plants during stress tolerance made it difficult to understand. Here, this thesis reports that Aux/IAA proteins interact with CaM in a Ca2+-dependent manner. The putative CaM binding domains (CaMBDs) were identified on all the available Aux/IAA proteins in Arabidopsis genome using Helical Wheel Projection program. The results revealed that most of the Aux/IAA proteins contain two putative CaMBDs on both domain I and II. In certain Aux/IAA proteins a single putative CaMBD was identified on either domain I or II, while IAA20 and IAA30 did not have any putative CaMBD. In most of the cases, the CaMBDs overlap with the EAR motif in domain I and auxin receptor binding motif or degron motif in domain II. Pull-down reactions and yeast two hybrid assays used during the study demonstrated that domain I and II of IAA7 interact with CaM in Ca2+-dependent manner. Furthermore, the experiments carried out using HS
Keywords: auxin, Aux/IAA transcription repressors, SAUR, calmodulin, calcium, domain I, domain II, biotic stress, abiotic stress